Heroes in Their Mirrors: An Examination of The Wars and Famous Last Words - Stewart, Janice (My University, 1992)
To discover Robert Raymond Ross' and Hugh Selwyn Mauberley's motivations for situating their fantasies within a framework of war, this thesis examines The Wars and Famous Last Words from a psychoanalytic and formalistic perspective. The first chapter of this thesis examines Ross' and Mauberley's compulsions to repeat, through displacements, the pre-war deaths of family members, and their compulsions' origins within the Oedipus complex. The second chapter explicates the ramifications of Mauberley's inability to resolve his Oedipal conflict. The fourth chapter probes the protagonists' identification with deities of Judaeo-Christian theology. The concluding chapter explores how war functions as an externalized metaphor for the inner conflicts of Ross and Mauberley.
Keywords: English Language and Literature; English Language and Literature